Strategi Digital Public Relations oleh Komunitas Lokal dalam Pemulihan Citra Wisata Tumpak Sewu Lumajang Pasca Penurunan Kunjungan - Ferdian Fikri Amirullah; Jupriyono .; Moh. Dey Prayogo (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study aims to analyze the Digital Public Relations (Digital PR) strategy implemented by the local community Pokdarwis Tumpak Sewu in restoring the tourism image of Tumpak Sewu Waterfall in Lumajang after a decline in visitor numbers. The main problem identified was the loss of public trust due to safety concerns and the lack of consistent digital promotion. This research employed a qualitative descriptive approach, collecting data through in-depth interviews, field observations, and social media documentation. Data analysis used the Miles and Huberman model, including data reduction, display, and conclusion drawing. The results show that the Digital PR strategy conducted by the community followed four stages proposed by (Cutlip & Broom, 2006): fact-finding, planning and programming, taking action and communicating, and evaluation. Through this strategy, the community successfully rebuilt the destination’s image by sharing positive messages, maintaining two-way communication with visitors, and increasing both digital engagement and tourist visits. The study concludes that community based Digital PR is effective in restoring tourism image and serves as a sustainable communication model for local tourism development.